PANDANGAN MASYARAKAT SEI KEPAYANG TERHADAP ILMU PERBANDINGAN AGAMA - Indra Harahap; Lidia Afni (UIN Sumatera Utara Medan, 2022)
Religion and religious life are inseparable elements of human life and the cultural system of mankind. Since the beginning of human culture, religion and religious life have been symptomatic in life, even giving the style and form of all cultural behavior. Religion and religious behavior grow and develop from a sense of human dependence on supernatural powers that they feel as the source of their life. Comparative Religion Science is a science that studies the origin of the formation of a religion, the characteristics and structure of a religion as well as what problems are contained in that religion. It is also stated that, Comparative Religion is a branch of science that has an effort to investigate the symptoms and understand the religious aspects or attitudes of a belief as well as its relationship with other religions including similarities and differences. Thus, it will be possible to compare a religion/belief with other religions/beliefs with the aim of recognizing various religions/beliefs and also being able to mediate between the problems that exist in the religious community. So far, the people of Sei Kepayag are still very layman and most of them do not know or even know nothing about Comparative Religion.